Phorophyte Diversity, Substrate Requirements and Fruit Set in Dendrobium scabrilingue Lindl. (Asparagales: Orchidaceae): Basic Observations for Re-introduction Experiments - WATTHANA, SANTI; PEDERSEN, HENRIK ÆRENLUND (Tropical Natural History, 2008)
In February-March 2007 a population of the epiphytic orchid, Dendrobium scabrilingue, from Salawin Wildlife Sanctuary (province of Mae Hong Son, northern Thailand), was studied with regard to substrate diversity, demography and fruit set. Among the 10 tree species that occurred in the 50 × 50 m study plot, all but Aporosa villosa served as phorophytes for D. scabrilingue. The orchid was found growing at (1-)2-4(-7) m above the ground, usually on bark densely covered with lichens (Aporosa villosa was the only tree species with bark consistently devoid of lichens). The orchid population was dominated by small individuals, thus demonstrating successful reproduction by seed. As indicated by a positive correlation between plant size and frequency of flowering, larger individuals appear to be of major importance for the sexual reproduction. A low relative fruit set in the population (18.5 %), and the shape of a Lorenz curve plotted from fruit set data, suggest a mainly allogamous breeding system operated by insects (probably bees, judging from the floral morphology). Based on our observations of this natural population, specific recommendations are given that may increase the success rates in re-introduction experiments with the rare D. scabrilingue.